2003
DOI: 10.1097/00004694-200309000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Slip Progression After In Situ Single Screw Fixation for Stable Slipped Capital Femoral Epiphysis

Abstract: The medical records and frog-leg lateral radiographs of 37 children with 46 stable slips treated with in situ single cannulated screw fixation at the Shriners Hospitals for Children, Lexington, from 1990 to 1998 were reviewed. The first postoperative frog-leg lateral radiograph was used to determine the head-shaft angle, the screw position, and the number of screw threads that engaged the epiphysis. The mean age at surgery was 12.3 years. The mean age when a frog-leg lateral radiograph first demonstrated physe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Carney et al (2003) found that 20% suffered a slip progression of 10° or more when operated with a single cannulated screw. The idea that double screw fixation is more likely to provide torsional stability in non-reduced slips than a single screw has been verified in artificially created slips in bovine femurs (Segal et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carney et al (2003) found that 20% suffered a slip progression of 10° or more when operated with a single cannulated screw. The idea that double screw fixation is more likely to provide torsional stability in non-reduced slips than a single screw has been verified in artificially created slips in bovine femurs (Segal et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Chondrolysis was defined as more than 50% reduction of minimal joint space compared to the contralateral side (Loder et al 2000). Slip progression was defined as an increased lateral epiphyseal shaft angle by more than 10° from surgery to final follow-up at skeletal maturity (Carney et al 2003). In accordance with Jerre, we considered a lateral epiphyseal-shaft angle above 13° in the asymptomatic, contralateral hip to be diagnostic of a silent slip (Loder et al 1993, Jerre et al 1994).…”
Section: Methodsmentioning
confidence: 99%
“…With the epiphysis being small, only a limited number of screw threads would engage the femoral head epiphysis. Carney et al showed progressive slippage in patients with slipped capital femoral epiphysis when less than five threads engaged the proximal femoral epiphysis [ 22 ]. This group of patients requiring revision of the transphyseal screw to recapture the proximal femoral physis still made improvements in head–shaft angle and physeal orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Upasani et al reported that maximum stability was gained when 40%-60% of the threads engaged the epiphysis using a 16 mm-thread single screw [ 18 ]. Carney et al recommended that five or more threads should engage the epiphysis [ 24 ]. In our study, the distribution of the threads was not a prognostic factor.…”
Section: Discussionmentioning
confidence: 99%